Universidade aberta à terceira idade: relato de experiência da Unati Assis - Geraldi, Ana Vitória Borges [UNESP] (2015)
This paper aims to present and reflect about the Extension Project "Universidade Aberta à Terceira Idade – UNATI" developed at the Faculdade de Ciências e Letras – UNESP Assis, for over two decades. The project, registered and funded by the Pró-reitoria de Extensão, currently, offers 34 workshops / courses under the responsibility of 75 volunteers, with the participation of 332 elderly, many of whom participate in more than one activity, resulting in 794 enrollments. The coordination team consists by teachers, technical and administrative server and graduate students: Extension fellows and volunteers. The project of Unati allows the opportunity to intergenerational and interdisciplinary meetings, exchange of experiences between the oldest and the university population contributing to a more ethical and citizen formation.